Retinal blood flow in patients with primary open angle glaucoma and optic disc hemorrhage. - Hudson, Christopher; Espahbodi, Nadia; Shahidi, Ayda M; Yusof @ Alias, Firdaus; Cheng, Richard; Jong, Monica; Trope, Graham; Buys, Yvonne M; Flanagan, John G (Association for Research in Vision and Ophthalmology, 2014)
Purpose: To investigate total retinal blood flow (TRBF) and retinal blood flow (RBF) in the superior (S) and the inferior (I) retinal hemifields in patients with primary open angle glaucoma (POAG) both with and without disc hemorrhage (DH).